2010
DOI: 10.5194/acp-10-6471-2010
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of black carbon in Guangzhou, China, in summer 2006

Abstract: Abstract. In situ measurements of the mass concentration of black carbon (BC) and mixing ratios of carbon monoxide (CO) and carbon dioxide (CO 2 ) were made at Guangzhou, an urban measurement site in the Pearl River Delta (PRD), China, in July 2006. The average ± standard deviation (SD) concentrations of BC, CO, and CO 2 were 4.7±2.3 µgC m −3 , 798±459 ppbv, and 400±13 ppmv, respectively. The trends of these species were mainly controlled by synoptic-scale changes in meteorology during the campaign. Based on b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
46
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 66 publications
15
46
1
Order By: Relevance
“…This ratio is consistent with a fossil-fuel-dominated carbonaceous aerosol, as is typically observed at urban sites, e.g. 5.7 ± 0.9 (Tokyo; Kondo et al, 2006), 5.4 ± 0.4 (Guangzhou;Verma et al, 2010), 5.8 ± 1.0 (Houston, Dallas; Spackman et al, 2008), and 3.5-5.8 (Beijing; Han et al, 2009), and somewhat lower than values found for periods when urban air masses are polluted by diesel traffic emissions: 7.9 ± 0.2 (Guangzhou; Andreae et al, 2008b), 7.7 ± 0.2 (Beijing, fall; Wang et al, 2011), and 8.4 ± 0.4 (North China Plain; Wang et al, 2011) (Table 3).…”
Section: Polluted Winter Airsupporting
confidence: 86%
“…This ratio is consistent with a fossil-fuel-dominated carbonaceous aerosol, as is typically observed at urban sites, e.g. 5.7 ± 0.9 (Tokyo; Kondo et al, 2006), 5.4 ± 0.4 (Guangzhou;Verma et al, 2010), 5.8 ± 1.0 (Houston, Dallas; Spackman et al, 2008), and 3.5-5.8 (Beijing; Han et al, 2009), and somewhat lower than values found for periods when urban air masses are polluted by diesel traffic emissions: 7.9 ± 0.2 (Guangzhou; Andreae et al, 2008b), 7.7 ± 0.2 (Beijing, fall; Wang et al, 2011), and 8.4 ± 0.4 (North China Plain; Wang et al, 2011) (Table 3).…”
Section: Polluted Winter Airsupporting
confidence: 86%
“…However, the lower BC/ CO ratio obtained over megacities such as Beijing and Shanghai is due to the higher number of gasoline and diesel vehicles (Zhou et al, 2009). The ratios obtained at Lumbini are within the range of emission ratios from diesel used in transport sector (0.0013-0.055), coal (0.0019-0.0572) and biofuels (0.0087-0.0266) for domestic activities (Verma et al, 2010, and references therein), implying that BC and CO observed are from mixed sources.…”
Section: Meteorologysupporting
confidence: 61%
“…Much research has focused on these experimental results (Verma et al, 2010;Fan et al, 2011). In this study, the observations at Guangzhou site ( Fig.…”
Section: Data Descriptionmentioning
confidence: 96%